Evaluation of physicochemical, microbiological and cutaneous permeation properties of Calendula officinalis L. In different concentrations and dosage forms - Valandro, Karina; Johann, Liana; Ely, Luisa Scheer; Herber, Jane; Rigo, Marines Persigo Morais (Seven Editora, 2023)
C. officinalis is a herbaceous plant that has anti-ulcerative, healing, restorative, anti-edematous and refreshing properties. In this article, the permeation of the glycolic extract of C. officinalis in cream and gel at different concentrations was evaluated. Accelerated stability tests were also carried out, as well as organoleptic, physical-chemical and microbiological tests. DOI:https://doi.org/10.56238/sevened2023.004-049